ASSESSMENT OF HEAVY METAL POLLUTION IN Clarias agboyiensis and Synodontis clarias IN EPE AND LEKKI LAGOONS, NIGERIA - EITOKPAH, E. P; CHUKWU, L. O; LAWAL-ARE, A. O; BASSEY, O.B (Nigerian Journal of Fisheries, 2018)
Heavy metal pollution has generated serious concern across the globe. Fishes exposed to polluted water may induce physiological changes, which serve as a useful tool for assessing the health status of aquatic ecosystems. This study assessed the heavy metal pollution in Clarias agboyiensis and Synodontis clarias from Epe and Lekki lagoons. Samples were collected from pollution hotspots of the lagoons to evaluate the levels of heavy metals- lead (Pb), Zinc (Zn), Cadmium (Cd) and Iron (Fe) in liver, gills and gonads of Clarias agboyiensis and Synodontis clarias from Epe and Lekki Lagoons. Four sampling sites were established in each lagoon for four ecological seasons. The mean levels of heavy metals showed significant differences (p<0.05) in the organs (gill, gonad and liver) and below permissible limit by WHO. The levels of heavy metals were in the order; Fe > Zn > Pb > Cd as well as liver > gill > gonad Clarias agboyiensis and Synodontis clarias from Epe and Lekki Lagoons. This is an indication that the gonad, gill and liver are good reflector of accumulated heavy metal pollutant from aquatic ecosystems. This study would serve as complimentary tools in the biomonitoring of the aquatic ecosystem. Keywords:, ,